Kajian Kelayakan Potensi dan Infrastruktur Desa Wisata Lantebung sebagai Tujuan Wisata Alam dan Edukasi - Asya Karima; Nia Angelina Bombong; Nurfaizah; Abdu Rahman (Wonderful-Journal of Tourism Destination, 2026)
Abstract This research assesses the feasibility of Lantebung Tourism Village as a natural and educational tourism destination based on mangrove ecosystems. The main problem raised was the unoptimal utilization of natural potential as well as the limited infrastructure and supporting institutions. A qualitative approach was used through in-depth interviews, field observations, and documentation studies with purposive sampling techniques. The results showed that the village has educational tourism potential, such as mangrove trekking and utilization of mangrove-based local products. However, infrastructure such as tracking paths, toilets, and information facilities are inadequate, and the role of Pokdarwis has not been optimized. Local community support such as JEKOMALA and IKAL are quite active in environmental conservation, but still need capacity building and cross-sector collaboration. This study concludes that Lantebung Village has the feasibility to be developed as a sustainable tourism destination with a note of the need for infrastructure revitalization and institutional strengthening. Keywords: nature tourism, education, mangrove, infrastructure, institutions. Abstrak Penelitian ini menilai kelayakan Desa Wisata Lantebung sebagai destinasi wisata alam dan edukasi berbasis ekosistem mangrove. Permasalahan utama yang diangkat adalah pemanfaatan potensi alam yang belum optimal serta keterbatasan infrastruktur dan kelembagaan pendukungnya. Pendekatan kualitatif digunakan melalui wawancara mendalam, observasi lapangan, dan studi dokumentasi dengan teknik purposive sampling. Hasil penelitian menunjukkan bahwa desa ini memiliki potensi wisata edukatif, seperti susur mangrove dan pemanfaatan produk lokal berbasis mangrove. Namun infrastruktur seperti jalur tracking, toilet, dan fasilitas informasi belum memadai, serta peran Pokdarwis belum berjalan optimal. Dukungan komunitas lokal seperti JEKOMALA dan IKAL cukup aktif dalam pelestarian lingkungan, namun masih memerlukan penguatan kapasitas dan kolaborasi lintas sektor. Penelitian ini menyimpulkan bahwa Desa Lantebung memiliki kelayakan untuk dikembangkan sebagai destinasi wisata berkelanjutan dengan catatan perlunya revitalisasi infrastruktur dan penguatan kelembagaan. Kata kunci: wisata alam, edukasi, mangrove, infrastruktur, kelembagaan.